Qualidade de vida e codependência em familiares de usuários de drogas - de Campos Moreira, Taís; Borges Bortolon, Cassandra; Fernandes, Simone; Signor, Luciana; Machado, Cássio; Rizzieri Figueiró, Luciana; Ferigolo, Maristela; Maria Tannhauser Barros, Helena (Revista Vozes dos Vales: Publicações Acadêmicas, 2015)
Substance use by one family member can negatively impact the quality of life of the entire family. A cross-sectional study was conducted with family members of drug users who contacted a telemedicine service. The WHOQOL-BREF and the Holyoake Codependency Index were used to assess quality of life and codependency. Fifty-two family member records were analyzed, and 94.2% were women. The average codependency index was 9.9 ± 2.4; family members with high codependency showed lower quality of life scores compared to family members with low codependency (P < 0.05), except in the domain of social relationships. The significant impact of substance use on the family member's quality of life demonstrates the need for care for the family as well as the user.
Keywords: Family; Quality of life; Mimetic dependence; Substance use disorders